PERMAINAN TEMPEL URUTKAN (TELUR) BERBANTUAN MEDIA KERTAS WARNA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENJUMLAHAN PECAHAN - Yulandari, Prida; Kurnia, Dadang; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
Initial research conducted on students of grade V SDN 1 Kepongpongan about mathematics subject matter that is the addition of fractions to get the value of learning outcomes that have not been satisfactory.Therefore, there should be efforts made to overcome the problem is by doing game Paste Sort (Egg) media colored paper aid in learning about the addition of fractions. Research method used in this research is Classroom Action Research (PTK). According to preliminary data of student learning result, obtained as many as 6 students or 17% is stated thoroughly and 29 other students or about 83% expressed unfinished. In the first cycle has increased, as many as 16 students or about 46% passed and 19 other students or about 54% declared unfinished. In the second cycles, increased by quite drastically as many as 35 students or 100% expressed in learning.Â